1990
DOI: 10.1159/000168196
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factors in Nephrotic Syndrome

Abstract: Nephrotic syndrome (NS) is associated with several disorders of hemostasis: thrombocytosis and platelet hyperaggregability; increased plasma levels of factors V and VIII, and of fibrinogen with blood hyperviscosity; decreased plasma levels of natural anticoagulants: free protein S, and antithrombin III compensated by increased levels of α2-macroglobulin; lowered fibrinolytic activity. Intensity of hypercoagulability is related to the degree of hypoalbuminemia; however, the role of hypercoagulability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 24 publications
1
33
0
1
Order By: Relevance
“…In addition, the insertion of an inferior vena caval filter did not halt the thrombotic alterations in the coagulation inhibitors (deficiency of ATIII, often, but not always, reduced functional levels process and caval thrombosis developed. The net effect of heparin in the presence of a low concentration of of protein C and S despite increased total levels); and platelet dysfunction [11,12]. It has been shown that all antithrombin III in the nephrotic state may therefore be insufficient or even adverse in terms of thrombin these disturbances have a general tendency to correlate with the degree of hypoalbuminaemia.…”
Section: Casementioning
confidence: 99%
“…In addition, the insertion of an inferior vena caval filter did not halt the thrombotic alterations in the coagulation inhibitors (deficiency of ATIII, often, but not always, reduced functional levels process and caval thrombosis developed. The net effect of heparin in the presence of a low concentration of of protein C and S despite increased total levels); and platelet dysfunction [11,12]. It has been shown that all antithrombin III in the nephrotic state may therefore be insufficient or even adverse in terms of thrombin these disturbances have a general tendency to correlate with the degree of hypoalbuminaemia.…”
Section: Casementioning
confidence: 99%
“…Increased levels of high-molecularweight coagulation factors such as fibrinogen, V, VII, VIII and X have been documented [18][19][20] and this increase is thought to result from increased hepatic synthesis of these factors, stimulated by hypoalbuminemia [21]. Factors IX, XI and XII are decreased possibly due to their urinary losses being of small molecular size [22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Since Kanfer [1]reported various disorders of the hemostatic system in patients with nephrotic syndrome, studies have attempted to elucidate the mechanisms of this hypercoagulable state. Alterations in blood coagulation factors, anticoagulants, and platelets have been reported.…”
Section: Introductionmentioning
confidence: 99%